Accuracy of maxillary full‐arch digital impressions of tooth and implant models made by two intraoral scanners - Hakimeh Siadat; Foujan Chitsaz; Somayeh Zeighami; Alireza Esmaeilzadeh (Wiley, 2024)
Abstract Objectives Limited studies are available on the accuracy of intraoral scanners (IOSs) for full‐arch implant and tooth models. This study aimed to assess the accuracy of maxillary full‐arch digital impressions of tooth and implant models made by two IOSs. Materials and Methods This in vitro, experimental study was conducted on two maxillary dentiform models: one with six prepared natural teeth and the other with six implants at the site of canine, first premolar, and first molar teeth, bilaterally. A highly accurate industrial scanner was used for actual measurements on the models that served as the reference scan. TS (Trios3) and CO (CEREC Omnicam) IOSs were then used to scan each model 10 times according to the manufacturer's instructions. All scans were saved in STL format. The GOM Inspect software was used according to the best‐fit algorithm to compare the accuracy of measurements in the groups with the reference scan. The trueness and precision were calculated. Statistical analyses were carried out using SPSS by one‐way analysis of variance and t‐test (α = .05). Results TS showed a significantly higher trueness than CO for both tooth and implant models (p < .05). TS also revealed significantly higher precision than CO for the tooth model; however, the difference in precision for the implant model was not significant between the two IOSs (p > .05). Conclusions TS showed higher accuracy than CO in both tooth and implant models.